2007
DOI: 10.1007/s11427-007-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological character of human adipose-derived adult stem cells and influence of donor age on cell replication in culture

Abstract: To investigate the biological character of human adipose-derived adult stem cells (hADAS cells) when cultured in vitro and the relationship between hADAS cell's replication activity and the donor's age factor, and to assess the stem cells as a new source for tissue engineering. hADAS cells are isolated from human adipose tissue of different age groups (from adolescents to olds: <20 years old, 21-40 years old, 41-60 years old and >61 years old groups). The protein markers (CD29, CD34, CD44, CD45, CD49d, HLA-DR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
1
17
2
Order By: Relevance
“…About CD34 expression, there are many different (14), ADSCs after being subcultured from P20 every 14 days reports. 10,18,28,29 Some researchers reported that ADSC can express CD34, 18,28 but this is different from our results and of some others. 10,29 It is possible that at the early time of culture, some hematopoietic cells may be mixed with the cultured cells.…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…About CD34 expression, there are many different (14), ADSCs after being subcultured from P20 every 14 days reports. 10,18,28,29 Some researchers reported that ADSC can express CD34, 18,28 but this is different from our results and of some others. 10,29 It is possible that at the early time of culture, some hematopoietic cells may be mixed with the cultured cells.…”
contrasting
confidence: 99%
“…8 While others obtained different numbers of ADSCs from adipose tissue with some different methods. 9,10 All these data indicate that with diverse isolation methods, different amount of ADSCs could be obtained from equal quantities of adipose tissue. If we want to obtain enough high quality cells for tissue engineering and regeneration therapy, a better and simple isolation method must be developed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations